Tinjauan Literatur: Efektifitas Pembelajaran Berdiferensiasi dalam Pembelajaran IPS di Sekolah Menegah Pertama - Zifa Nabilla Zahra; Desy Safitri; Sujarwo (PT. Penerbit Tiga Mutiara, 2025)
Differentiated instruction is a pedagogical approach aimed at addressing the individual needs of students by adapting teaching strategies based on differences in ability, interests, and learning styles. This approach is increasingly relevant in the context of junior high schools, where classroom diversity necessitates more adaptive and inclusive teaching methods. This study aims to analyze the implementation of differentiated instruction in Social Studies subjects and assess its contribution to the quality of both the learning process and its outcomes. The method employed is a systematic literature review, identifying and analyzing scholarly articles obtained through the Publish or Perish software, which utilizes Google Scholar, focusing on publications from 2016 to 2025. The findings indicate that the application of differentiated instruction has a significantly positive impact on enhancing student engagement, academic achievement, the development of critical thinking skills, and a deeper understanding of concepts in Social Studies. This approach also succeeds in fostering an inclusive, adaptive, and participatory learning environment that encourages intrinsic motivation and boosts students’ self-confidence. The study emphasizes that the success of differentiated instruction heavily depends on teachers' ability to design and implement data-driven, responsive teaching strategies tailored to each student's needs. These findings are expected to serve as practical guidance for teachers in developing more effective instruction, enrich the academic discourse in the field of differentiated pedagogy, and contribute to the formulation of education policies that support diversity and equity in junior high school learning processes.